The enhanced ferromagnetism of single-layer CrX3 (X = Br and I) via van der Waals engineering. Issue 22 (28th May 2019) - Li, Hongxing; Xu, Yuan-Kai; Lai, Kang; Zhang, Wei-Bing
Abstract : The ferromagnetism of CrI3 and CrBr3 is enhanced by interlayer coupling. Abstract : The recent experimental discovery of intrinsic ferromagnetism in single-layer CrI3 opens a new avenue to low-dimensional spintronics. However, the low Curie temperature, T C ∼ 45 K, is still a large obstacle to its realistic device application. In this work, we demonstrate that the T C and magnetic moment of CrX3 (X = Br, I) can be enhanced simultaneously by coupling them to buckled two-dimensional Mene (M = Si, Ge) to form magnetic van der Waals (vdW) heterostructures. Our first-principles calculations reveal that n-doping of CrX3, induced by a significant spin-dependent interlayer charge-transfer from Mene, is responsible for the drastic enhancement of T C and magnetic moment. Furthermore, the diversified electronic properties including half-metallicity and semi-conductivity with a configuration-dependent energy gap are also predicted in this novel vdW heterostructure, implying broad potential applications in spintronics. Our study suggests that vdW engineering may be an efficient way to tune the magnetic properties of 2D magnets, and Mene/CrX3 magnetic vdW heterostructures are wonderful candidates in spintronics and nanoelectronics devices.